Children's prayers from a Hospital Chapel - Langford, Lou (International journal of children's spirituality, 2015)
Children's prayers, from prayer books left in the Chapel of a Children's Hospital between 1998 and 2002, were studied for what the children's God-talk would reveal about their perceptions of God. Of the 3893 prayers written during this period, 346 were confidently identified as being authored by children. The sample of 346 prayers, which gave rise to 558 expressions of prayer, was explored through a content analysis, used quantitatively to summarise and describe the data, and a thematic analysis, informed by methods from Grounded Theory. The psychological and spiritual significance of the prayers is drawn out, demonstrating the richness and relationality of children's spirituality. The predominance of prayers written by female writers, suggests that the extent to which relationality is present is related to gender. Questions concerning possible gender-related differences in girls' and boys' spirituality are raised and implications for practice are considered.